2006
DOI: 10.1309/hpyg-flnx-kfbh-dqev
|View full text |Cite
|
Sign up to set email alerts
|

Primary CD20+CD10+CD8+ T-Cell Lymphoma of the Skin With IgH and TCRβ Gene Rearrangement

Abstract: Most cutaneous T-cell lymphomas are derived from mature postthymic T cells of the CD4 subtype. When other less common profiles are encountered, a diagnostic challenge is posed. Accurate categorization is critical because of the specificity of therapeutic regimens, including biologics. A 65-year-old woman was seen in 2001 because of a thigh mass manifesting an unusual phenotype eventually categorized as a mature postthymic CD8+ T-cell lymphoma with CD10 and weak CD20 expression. Molecular studies revealed T-cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
30
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 29 publications
1
30
0
Order By: Relevance
“…The expression of TIA-1 and CD7 was not reported in this case. 10 Recently, Sen et al 11 reported a case of mycosis fungoides in the lower extremity that expressed CD20. Similar to the current case, a clonal T-cell receptor g-chain gene rearrangement was present, but no rearrangements of the immunoglobulin heavy or light chain genes were found, and there was lack of CD7 expression.…”
Section: Discussionmentioning
confidence: 99%
“…The expression of TIA-1 and CD7 was not reported in this case. 10 Recently, Sen et al 11 reported a case of mycosis fungoides in the lower extremity that expressed CD20. Similar to the current case, a clonal T-cell receptor g-chain gene rearrangement was present, but no rearrangements of the immunoglobulin heavy or light chain genes were found, and there was lack of CD7 expression.…”
Section: Discussionmentioning
confidence: 99%
“…This case expressed the T-cell-associated antigens CD3 and CD8 and had a clonal T-cell receptor (TCR) γ chain rearrangement without evidence of clonal rearrangements of immunoglobulin genes. More recently, a case of primary T-cell lymphoma of the skin with coexpression of CD20 and dual immunoglobulin and TCR gene rearrangement has been reported [15].…”
Section: Introductionmentioning
confidence: 99%
“…Among 37 cases, 12 cases underwent chemotherapy as a first-line therapy, according to the limited description of literatures, and interestingly, rituximab was administered in 10 out of the 12 cases. Thus, rituximab has been administered in 11 patients with CD20-positive PTCL-NOS, including our case (Table 1) [4,18,21,[25][26][27][28][29]. Among 11 cases, 8 (72.7 %) occurred in males, and the number of patients at 65 or more than 65 years of age was 8.…”
Section: Discussionmentioning
confidence: 93%
“…However, in our case, the sample size through endoscopy was inadequate to flow cytometric analysis. In our knowledge, only one case of CD20-positive PTLC with the dual rearrangement has been reported [18].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation